THE MOST IMPORTANT PHENOMENA OF THE ARABIC LANGUAGE IN THE MEDIA BETWEEN (warning and development) - Ashour, Hani Ibrahim (ALBAHITH ALALAMI, 2020)
Summary of the research : Our research tagged (Arabic language in the media between warning and development) attempts to follow the most prominent phenomena that accompanied the evolution of the use of Arabic language in the media with the development of these means and spread technically globally, and how divided researchers and linguists and intellectuals Arabs into two teams, each demanding what contradicts the other, in the matter The use of the Arabic language in the media, and the arguments of each team in the need to deal with the media as one of the pillars of the nation culturally, historically and civilized, in order to enhance its position and maintain unity, continued the research highlighted the positions of hard-liners keen to maintain the integrity of the Arabic language Atha rich, also followed the positions of the other team, which calls for the development of the use of the Arabic language to ensure that keep pace with global developments in the field of media and achieve the spread between the Arab community and the production of new methods of categories of language private media to ensure ease of use of the Arabic language and enhance its growth and spread.